2013
DOI: 10.1593/tlo.13133
|View full text |Cite
|
Sign up to set email alerts
|

CXCR2 Macromolecular Complex in Pancreatic Cancer: A Potential Therapeutic Target in Tumor Growth

Abstract: The signaling mediated by the chemokine receptor CXC chemokine receptor 2 (CXCR2) plays an important role in promoting the progression of many cancers, including pancreatic cancer, one of the most lethal human malignancies. CXCR2 possesses a consensus PSD-95/DlgA/ZO-1 (PDZ) motif at its carboxyl termini, which might interact with potential PDZ scaffold/adaptor proteins. We have previously reported that CXCR2 PDZ motif-mediated protein interaction is an important regulator for neutrophil functions. Here, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 41 publications
1
50
0
Order By: Relevance
“…The IL8-CXCR2 pathway has been shown to be important in the pathogenesis of solid tumors, and preclinical studies have demonstrated a role for this pathway in the breast cancer microenvironment. 22,27,28,30,45 Various small molecule CXCR2 inhibitors are being developed clinically, and one is being tested in a clinical trial in breast cancer. Our results demonstrate that this pathway is also functionally important for the viability of leukemic stem cell compartments in AML and MDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IL8-CXCR2 pathway has been shown to be important in the pathogenesis of solid tumors, and preclinical studies have demonstrated a role for this pathway in the breast cancer microenvironment. 22,27,28,30,45 Various small molecule CXCR2 inhibitors are being developed clinically, and one is being tested in a clinical trial in breast cancer. Our results demonstrate that this pathway is also functionally important for the viability of leukemic stem cell compartments in AML and MDS.…”
Section: Discussionmentioning
confidence: 99%
“…21 Blocking the IL8-CXCR1/CXCR2 axis has shown to be of therapeutic potential in a variety of solid tumors [27][28][29][30] ; however, there is little known of its role in hematologic malignancies. Our study reveals that IL8 is significantly overexpressed in AML and MDS LT-HSCs, ST-HSCs, and GMPs compared with healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Growth factor reduced Matrigel matrix, glutathione agarose beads and Transwell inserts were purchased from BD Bioscience. The human and murine CXCR2 C-tail peptides (biotin-conjugate at N-terminus): WT (biotin-FVGSSSGHTSTTL for human CXCR2 C-tail; and Biotin-FVSSSSANTSTTL for mouse CXCR2 C-tail) and PDZ motif deletion (ΔTTL) were synthesized by Genemed Synthesis, Inc. (San Antonio, TX), and used as reported before (Wu et al, 2012;Wang et al, 2013). SB225002 was purchased from Tocris Bioscience.…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
“…Of note, both human and murine CXCR2 possess a consensus PDZ motif at their carboxyl termini. We have recently reported that the PDZ motif (TTL) of CXCR2 is involved in the regulation of intracellular signaling and cellular functions in neutrophils (Wu et al, 2012) and pancreatic cancer cells (Wang et al, 2013). We showed that CXCR2 and its downstream signaling molecule PLC-β are clustered by a PDZ adaptor protein NHERF1 which scaffolds a CXCR2-PLC-β complex through PDZ-mediated interactions (Wu et al, 2012;Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation